Rice plants respond to ammonium stress by adopting a helical root growth pattern. (22nd September 2020) - Jia, Letian; Xie, Yuanming; Wang, Zhen; Luo, Long; Zhang, Chi; Pélissier, Pierre‐Mathieu; Parizot, Boris; Qi, Weicong; Zhang, Jing; Hu, Zhubing; Motte, Hans; Luo, Le; et al.
SUMMARY: High levels of ammonium nutrition reduce plant growth and different plant species have developed distinct strategies to maximize ammonium acquisition while alleviating ammonium toxicity through modulating root growth. To date, the mechanisms underlying plant tolerance or sensitivity towards ammonium remain unclear. Rice ( Oryza sativa ) uses ammonium as its main N source. Here we show that ammonium supply restricts rice root elongation and induces a helical growth pattern, which is attributed to root acidification resulting from ammonium uptake. Ammonium‐induced low pH triggers the asymmetric distribution of auxin in rice root tips through changes in auxin signaling, thereby inducing a helical growth response. Blocking auxin signaling completely inhibited this root response. In contrast, this root response is not activated in ammonium‐treated Arabidopsis. Acidification of Arabidopsis roots leads to the protonation of indole‐3‐acetic acid and dampening of the intracellular auxin signaling levels that are required for maintaining root growth. Our study suggests a different mode of action by ammonium on the root pattern and auxin response machinery in rice versus Arabidopsis, and the rice‐specific helical root response towards ammonium is an expression of the ability of rice to moderate auxin signaling and root growth to utilize ammonium while confronting acidic stress. Significance Statement: In this study, we discovered a helical response of the rice root in response to the acidic stress resulting from root ammonium uptake. Ammonium‐induced acidic stress triggers the asymmetric distribution of auxin at rice root tips through modulating auxin signaling pathways, thereby inducing a helical root response.